An algorithm for ranking quickest simple paths - Pascoal, Marta M. B. (2005)
In this paper, an algorithm for ranking loopless paths in undirected networks, according to the transmission time, is presented. It is shown that the worst-case computational time complexity of the algorithm presented is , which is also the best-known complexity to solve this problem. The worst-case memory complexity is , which improves the existing algorithms. Finally, comparative computational results, with other algorithms for the same problem, are reported.